Work-life balance mediating stress and quality of life in academics during COVID-19 in Malaysia - Lwin M. Aye; Jeremy Ern Hwei Tan; Shamala Ramasamy (Journal of Public Health in Africa, 2024)
Background: Following the implementation of the Movement Control Order (MCO) during the coronavirus disease 2019 (COVID-19) pandemic, academicians from the universities in Malaysia needed to ensure that the quality-of-service delivery to the stakeholders is undisturbed by adopting new challenging norms. This compromises the work-life balance (WLB), causes more stress and potentially affects their quality of life (QoL).